You are on page 1of 9

1

Assignment 7 — Solutions 3/7/04

Problem 5.2

(a) For a single loop of current I on the x-y plane centered at the origin and observation point at f = 0:

÷÷” 1 =

B

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ m 0 I 4 p

÷÷ W ,

W

=

® S

÷÷ R ÿ a ÷£

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

R 3

 a ÷”£ = v £ v £ f £ z `£ ” ` ` x = v v + z z ,

x £

v £ v £

= v £2 + v 2 + z 2 - 2 v £ v cos f £

÷÷ = x £ - x

`

=

x £ § 2 - x § 2 - 2 x £ ÿ x

R

,

 R 2 = For z ∫ 0: W = ∑W ÅÅÅÅÅÅÅÅÅÅÅÅ = ∑ z = ∑W ÅÅÅÅÅÅÅÅÅÅÅÅ = ∑v ∑W ÅÅÅÅÅÅÅÅÅÅÅÅ =

0

0

0

0

0

2 p f £ 0

2 p f £ 0

2

2

p f £ 0

p f £ 0

b

b

b v £

-z v £ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ Hv £2 + v 2 + z 2 - 2 v £ v cos f £ L 3ê2

v

£

j

jj-

k R 3

+

3

2

z v £

R

5

z

2 z y

{

b v £ i ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz

v £ -v £ Hv £2 + v 2 - 2 z 2 - 2 v £ v cos f £ L ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ Hv £2 + v 2 + z 2 - 2 v £ v cos f £ L 5ê2

z v £ H2 v - 2 v £ cos f £ L v £ 3 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

ÅÅÅÅÅ

2

Hv £2 + v 2 + z 2 - 2 v £ v cos f £ L 5ê2

∑f

z
R
da′
S
x
x′
x

y

We can imagine the solenoid to be made up of an infinite stack of circular current loops each carrying current I .

Since the system is azimuthally symmetric, fix the observation point x at f = 0, and since the solenoid is infinitely

long fix z = 0. The total magnetic field is the superposition of fields due to each loop, which we have from above as a function of relative position of the observation point from a given loop. Thus

÷÷ HvL = z N ÷÷

B

y

z

B 1 Hv, zL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z i ÅÅÅÅÅÅÅÅÅÅÅÅ + v ÅÅÅÅÅÅÅÅÅÅÅÅ z

∑v {

m 0 I N

4 p

`

j

jz

k

∑W

z

∑W

`

∑W ê ∑v is odd in z in the range -¶ < z < +¶, so that integral vanishes. ∑W ê z is even in the same range, so for some infinitesimal e > 0:

Printed by Mathematica for Students

2

m 0 I N

4

÷÷ HvL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

m 0 I N ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ p

B

=

-e z + -e J

e

-e

`

e z z ÅÅÅÅÅÅÅÅÅÅÅÅ

∑W

z

z + e z N i

`

∑W

z

j

jz ÅÅÅÅÅÅÅÅÅÅÅÅ

k

y

z

z

{

ì

-e z

=

Å

m 0 I N Å ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

Å

Å

Å

Å

ÅÅ

Ä

Ç

4 p

É

Ñ

Ñ Ñ Ñ Ñ `

ÑÑ z

lim + W - lim - W Ñ

zØ0

zØ0

Ö

=

e z

=

- e z

The splitting of ranges was necessary because W is discontinuous at z = 0, so ∑W ê z is proportional to a d-func- tion. For v > a (observation point outside solenoid) lim zØ0 W = 0 since no angle is subtended by a surface in the same plane but not inclusive of the observation point. For v < a, the area subtended approaches the entire hemisphere:

da′
R
ε
lim + W
=
2 p
zØ0
`
: m 0 I N z
÷÷” B HvL =
0
da′
−ε
R
lim - W=-2 p
zØ0
÷÷”
, v < a
B
ï H ÷÷÷” HvL ª
ÅÅÅÅÅÅÅÅÅ
,
v
> a
m 0

=

ï

:

`

I N z

0

,

,

lim + W - lim - W

zØ0

zØ0

v < a v > a

=

4 p

(b) Let's assume that a "realistic solenoid" is an infinite helix of outer radius a and with N turns per unit

length, its axis being the z-axis. For a circular Amperian loop concentric with the solenoid and with radius v > a, the plane of the loop is pierced exactly once by the wire (geometrical property of helical curves), so

÷÷ B ÿ l = 0 2 p a f B f Hv > a, f, zL = m 0 I

For any ÷÷ B -field related quantity f Hv, f, zL, define the average of f over a segment of length L of the solenoid as

X f Hv, f, zL\ ª A Ÿ z z+L z £ f Hv, f, z £ LE ë L. We can argue that X f \ is only a function of v in the limit L Ø ¶:

X f \ cannot depend on z because the solenoid is infinite so providing we average over enough turns X f \ should be invariant under translations in z, which can only be if it is independent of z.

X f \ cannot depend on f because when averaging over sufficiently many turns, a helix is symmetrical under rota- tions about its axis so the averaged quantity X f \ must also be independent of f.

Thus

Printed by Mathematica for Students

3

Xm 0 I\

1

ÅÅÅÅÅÅ

L

m 0 I L

m 0 I

XB f \ v>a

= ÅÅÅÅÅÅ z+L z £ m 0 I =

1

L z

1

ÅÅÅÅÅÅ

L

z

z+L z £ 0

2

p v f B f Ha, f, z £ L

=

=

=

0 2 p v f

1

ÅÅÅÅÅÅ

L

z

z+L z £ B f Ha, f, z £ L = 0 2 p v f XB f \ v>a

XB f \ v>a 0

m 0 I ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 p v

2

p v f

=

2 p XB f \ v>a

=

[ 0 2 p a f B f _

Similarly an Amperian loop of radius v < b, where b is the inner radius of the solenoid encloses no current, so XB f \ v<b = 0.

We

and z, for a cylindrical Gaussian surface concentric with the solenoid

can show by contradiction that XB v \ = 0 everywhere. Suppose that XB v \ 0. Since XB v \ is independent of f

V

3 x ÷÷ “ ÿ XB ÷÷ \ =

® S XB ÷÷ \ ÿ n

` a

= 0

r v 0 2 p v f HXB z \ z=z 0 +L - XB z \ z=z 0 L

+

z

z 0 +L z 0

0

2

p r f XB v \ v=r

z

0

+ L

z

0

z
r n ˆ
=
z ˆ
zz
= +
L
0
S
nˆ =
ϖ
ˆ
ϖ
n ˆ
=−
z ˆ
z
= z
0

=

The integrand in the first term vanishes since XB z \ is independent of z. XB v \ is independent of f and z so

V

3 x ÷÷

“ ÿ XB ÷÷ \ = 2 p r L XB v \ 0 ï “

÷÷ ÿ XB ÷÷ \

But this is a contradiction of the fact that

0

somewhere

÷÷” ÿ B

÷÷ =

0

ï

0

= Y ÷÷” ÿ B

÷÷” ] =

=

÷÷” ÿ i 1

j

jj ÅÅÅÅÅÅ

k 0

L

So it cannot be true that XB v \ 0.

1

ÅÅÅÅÅÅ

L

z

z+L z £

1

÷÷” ÿ B

÷÷ Hv, f, z £ L = ÅÅÅÅÅÅ

L

L z £ ÷÷ Hv, f, z £ L zz y = “

B

z

{

÷÷ ÿ XB ÷÷ \

0

L z £

÷÷” ÿ B

÷÷ Hv, f, z £ L

For a rectangular Amperian loop G lying on a f-constant plane with the "left" edge within the solenoid and the "right" edge off at infinity:

Printed by Mathematica for Students

4

G

÷÷ B ÿ l

m 0 I enc

I enc

= z

z 0 +L z £ HB z § v - B z § v+l L

0

=

=

+ v

L XB z \ + v

v+L v £ HB v § z 0 +L - B v § z 0 L

v+L v £ HB v § z 0 +L - B v § z 0 L

: NIL

0

,

,

v < b v > a

z
ϖˆ
−zˆ
−ϖˆ
l
ϖ

z

0

z 0

+ L

Xm 0 I enc \ = XL XB z \\ + v v+L v £ HXB v z 0 +L - XB v z 0 L ï m 0 I enc = L XB z \

Finally we get

`

l m 0 I N z

o o

v < b

,

XB ÷÷” \ = o

 m ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ m 0 I ` o o o f , v > a

n

2 p v

Problem 5.3

Let z be the distance from the observation point (chosen to be at the origin) to one of the loops in the solenoid (carrying current I flowing clockwise as seen in the x-y plane), which then subtends an angle q:

W

=

=

÷÷” W =

0

2 p f £ 0

q q £ sin q £

 2 p H1 - cos qL ∑W ` ÅÅÅÅÅÅÅÅÅÅÅÅ z ∑ z

=

-2 p 1 cos q Hcos q £ L

z

a
θ
0
θ
1
2
L 1
L 2

Integrate over all loops using the formula in problem 5.1 to get the magnetic field:

÷÷” =

B

=

-L 2

L 1 z N ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

m 0 I

4 p

÷÷” W =

-L 2

L 1 z

m 0 N I ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 4 p

∑W

ÅÅÅÅÅÅÅÅÅÅÅÅ

z

`

z

=

m 0 N I ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 4 p

HW § z=-L 2 - W § z=L 1 L

m 0 N I

m 0 N I

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ @2 p - cosHp-q 2 L - 2 p + cos q 1 D = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ Hcos q 1 + cos q 2 L

2

2

Printed by Mathematica for Students

5

Problem 5.6
BHvL 2 p v
÷÷” B =
1
ÅÅÅÅÅ
2
y
J = Jzˆ
d
a
x

For any cylinder of radius R with constant current density J ÷ = J z , Ampere's law for a circular loop G of radius

`

`

v < R concentric with the sylinder and on a constant-z plane gives [with ÷÷ B = B HvL f from azimuthal symmetry]:

= ® G ÷÷ ÿ l = m 0 S ÷ ÿ a ÷ = m 0 J p v 2

B

J

` 1

m 0 J v f

=

ÅÅÅÅÅ

2

m 0 J H- y x + x y L

`

`

Displacing the cylinder by x 0 along the x-axis is accomplished by substituting x Ø x - x 0 . By superposition

y
J′=−Jzˆ
d
=
x
+
b
y
J′′= J zˆ
x

÷÷” = ÷÷”

B

B £ + B

÷÷”

=

-

1

ÅÅÅÅÅ

2

1

m 0 J @- y x + Hx - dL y D + ÅÅÅÅÅ m 0 J H- y x + x y L

`

`

2

`

`

=

1

ÅÅÅÅÅ

2

m 0 J d y

`

,

v < b

Problem 5.14

Neglecting end effects we have a 2D problem, i.e. the z = 0 slice taking the cylinder axis as along the z-axis. J ÷ = 0

everywhere means we can write B

can be expanded in Legendre polynomials:

÷÷ = -“

÷÷ F where the magnetic scalar potential F satisfies Laplace's equation and

lim

vØ¶

F =

IA l v l + B l v -Hl+1L M P l Hcos fL

l=0

o l F I

o

o

oo

= m

o

o

o

oo

F

F

II

III

n

÷÷” =

B

`

B 0 x

,

,

,

ï

v § a

a §v§ b

b § v

lim

vØ F

=

B 0 x

=

B 0 v cos f

y
B
= B xˆ
0
0
Φ ΙΙΙ
Φ ΙΙ
Ι
Φ
x
a
b
µ
µ
0

The asymptotic form of F implies only the l = 1 term is nonzero in F III :

Printed by Mathematica for Students

6

F III

=

i

j

j

j B 0 v +

j

k

B

III

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

v

y

{

z

z cos f

z

z

Continuity at the II-III and I-II boundaries similarly restricts the expansions to the l = 1 terms. Also in region I finiteness at v = 0 forces us to drop the 1 ê v term:

F II

=

i

j A II v +

j

j

j

k

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

v

y

{

z

z cos fïF I

z

z

=

A I v cos f

The boundary conditions are that B ¦ = -∑F ê ∑v and H ˛ = -@1 ê m HvL vD ∑F ê ∑f be continuous:

 Region -B ¦ -H ˛ A III cos f 1 A III sin f I v§ a - ÅÅÅÅÅÅÅÅÅ m 0 II a §v§ b i j A II - j j j B II ÅÅÅÅÅÅÅÅÅÅÅ 2 y z z cos f z z - 1 ÅÅÅÅÅÅ i j A II + j j j B II ÅÅÅÅÅÅÅÅÅÅÅ 2 y z z sin f z z k v { m k v { III b § v i j j B 0 - j j B III ÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 y z z cos f z z - 1 ÅÅÅÅÅÅÅÅÅ i j j B 0 + ÅÅÅÅÅÅÅÅÅÅÅÅÅ j j B III 2 y z z sin f z z k v { m 0 k v {

v

= a

v

= b

A I

A II

B II

B III

=

=

=

=

:

:

A II -

A II +

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

a

B

2

II

ÅÅÅÅÅÅÅÅÅÅÅ

a

2

B

III

B 0 -

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

2

III

b

B

B 0 + ÅÅÅÅÅÅÅÅÅÅÅÅÅ

b

2

=

=

=

=

A III

m

0

ÅÅÅÅÅÅÅÅÅ

m

A III

=

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

b

i

j A II +

j

k

j

j

2

A II -

m

0

ÅÅÅÅÅÅÅÅÅ

m

4 m 0 m b 2 B 0 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

2 m Hm+m 0 L b 2 B 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

2 m Hm+m 0 L b 2 a 2 B 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

2

-b 2 Hm 2 + m 0 LHb 2 - a 2 L B 0 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

m

0

ÅÅÅÅÅÅÅÅÅ

m

i

j

j A II -

j

j

k

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

a

2

y

z

z

z z

{

ï

B II

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

b

2

=

=

y

z

z

z

z

{

ï

4 m 0 m b B 0

2

m Hm+m 0 L b B 0

B 0

B III

=

=

= 2 m Hm-m 0 L a 2 b B 0

=

2

-Im 2 + m 0 MIb 2 - a 2 M b B 0

=

a 2 i

m-m 0

j

j

j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

k

2 m 0

y

z

z

z A III

{

m 0 + m ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 m

A II +

m 0 - m ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 m

B

II

ÅÅÅÅÅÅÅÅÅÅÅ

b

2

b 2 i

m 0 - m

j

j

j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

k

2 m {

y

z z A II +

z

m 0 + m ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 m

B

II

b

ª

1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

Printed by Mathematica for Students

7

F I

F II

F III

=

=

=

4 m 0 m b B 0 cos f v

i

j

j

a 2 y

z

z

z

2 m b B 0 j Hm+m 0 L v + Hm-m 0 L ÅÅÅÅÅÅÅÅÅ z cos f

j

k

v

{

B 0 i

k

j

jv - Im 2 + m 0 MIb 2 - a 2 M ÅÅÅÅÅÅÅÅ z cos f

2

b

y

z

v {

 1 ∑F 1 ∑F Region H v = - ÅÅÅÅÅÅ m ÅÅÅÅÅÅÅÅÅÅÅÅ H f = - ÅÅÅÅÅÅÅÅÅÅÅÅÅ m v ÅÅÅÅÅÅÅÅÅÅÅ ∑f ∑v I -4 m b B 0 cos f 4 m b B 0 sin f i 2 y i 2 y II -2 b j j B 0 j Hm+m 0 L - Hm-m 0 L j k a ÅÅÅÅÅÅÅÅÅÅÅ v 2 z z cos f z z { 2 b j j a B 0 j Hm+m 0 L + Hm-m 0 L ÅÅÅÅÅÅÅÅÅÅÅ z sin f j k v 2 { z z z III B 0 - ÅÅÅÅÅÅÅÅÅÅ m 0 i j j1 - Im 2 + m 0 MIb 2 - a 2 M ÅÅÅÅÅÅÅÅÅÅÅ z cos f k 2 b v 2 y z { B 0 ÅÅÅÅÅÅÅÅÅÅ m 0 i j j1 - Im 2 + k m 0 MIb 2 - a 2 M ÅÅÅÅÅÅÅÅÅÅÅ z sin f 2 v 2 { b y z

Along the axis H

÷÷÷ § v=0 = 4 m b B 0 = B ÷÷ § v=0 ë m so B ÷÷ § v=0 = 4 m 2 b B 0 , i.e.

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ B ÷÷ § v=0

B 0

4 m 2 b 2

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

b 2 Hm 0 + mL 2 - a 2 Hm-m 0 L 2

4 m

2

r

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

log 10 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ B ÷÷ § v=0

B

0

Hm r + 1L 2 - Ha êbL 2 Hm r - 1L 2

= log 10 H4L + 2 log 10 Hm r L

-log 10 AHm r + 1L 2 - HaêbL 2 Hm r - 1L 2 E

log 10 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ B ÷÷ § v=0 B 0

4 a 2 êb 2 =0.5
log 10 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1 - Ha ê bL 2
a 2 êb 2 =0.1

log 10 Hm r

Problem 5.17

(a) and (b)

m r

÷ J Hx, y, zL

ª

=

÷ J * Hx, y, zL ª

m ê m 0

J x Hx, y, zL x + J y Hx, y, zL y + J z Hx, y, zL z

`

`

`

m r - 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ @J x Hx, y, -zL x + J y Hx, y, -zL y + J z Hx, y, -zL z D

m r + 1

`

`

`

We need to show that the field

Printed by Mathematica for Students

8

l

÷÷” > ª o B

o

o

o

o

oo

÷÷” B < ª

n

o

o

o

o

o

o

o

m

0

ÅÅÅÅÅÅÅÅÅÅÅ

4

m

p

0

ÅÅÅÅÅÅÅÅÅÅÅ

2 m r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

x - x £

3 x £ AJ ÷ Hx £ L + ÷

3 x £ J

J * Hx £ LEä ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

x - x

£

§ 3

x - x £

B

÷÷ Hx, y, zL ª m

÷ Hx £ Lä ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

x - x

£

§ 3

 4 p m r + 1 z > 0 z < 0

satisfies

÷÷” ä ÷÷”

B

l

o

m

n o

÷ m 0 J

0 ,

,

=

÷÷” ÿ ÷÷”

B

=

0

÷÷” > - B

IB

÷÷ < M ÿ z z=0

`

`

z

÷÷÷” > - H

äIH

÷÷÷” < M ÿ z

`

=

z=0

0

=

ï

0

>

B z

ï

§ z=0

=

B < z § z=0

m r B x

m

B y

>

>

r

§ z=0

z=0

=

=

B < x § z=0

<

B y

z=0

,

,

z ¥ 0

z § 0

(1)

(2)

(3)

(4)

(5)

(3) is automatic since we've written ÷÷ B in terms of currents. Since

÷÷” ä

m 0

ÅÅÅÅÅÅÅÅÅÅÅ

4 p

è

è

÷÷”

x - x £

3 x £ J Hx £ Lä ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = m 0 J Hx £ L

è

÷÷”

x - x

£

§ 3

for any J ÷” , we have

÷÷” ä ÷÷”

B

=

l

o

o

o

o

m

o

o

o

o

n

m 0 J ÷ + m 0 J ÷ *

2 m r

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

m r + 1

÷ m 0 J

=

=

m 0 J ÷

0

,

,

z > 0

z < 0

since J ÷ * § z>0 = 0 and J ÷ § z<0 = 0. Thus (2) is satisfied.

J ÷ äHx - x £ L

=

=

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ x - x £

ƒ

x @Hz - z £ L J y - Hy - y £ L J z D + y @Hx - x £ L J z - Hz - z £ L J x D + z

`

`

`

x

J x

`

y

J y

y - y £

`

z

J z

z - z £

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

§

ƒ

ƒ

ƒ

ƒ

ƒ

ƒ

`

@Hy - y £ L J x - Hx - x £ L J y D

For conciseness in the following integrals the arguments to a function f Hx £ , y £ , z £ L being integrated over will be suppressed when there is no ambiguity. The image function f Hx £ , y £ , -z £ L will be written as f H-z £ L.

B

>

z

r 0 ª "######################################## ##########

Hx - x + Hy - y + z £2

£

L

2

£

L

2

§ z=0

=

m

0

ÅÅÅÅÅÅÅÅÅÅÅ

4 p

3 x £ Hy - y £ L i jJ x Hz £ L + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

j

j

k

m r - 1

m r + 1

J x H-z £ L z y - Hx - x £ L i jJ y Hz £ L + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ J y H-z £ L y z z ÅÅÅÅÅÅÅÅ

z

z

{

j

j

k

m r - 1

m r + 1

z

{

1

3

0

r

Printed by Mathematica for Students

9

A change of variables -z £ Ø z £ takes

function g of r 0 only, since the range is over all space and r 0 is invariant under -z £ Ø z £ . Performing this on the integrals involving J i H-z £ L:

Ÿ x £ f Hx £ , y £ , -z £ L gHr 0 L = Ÿ x £ f Hx £ , y £ , z £ L gHr 0 L

for any function f and

B

>

z

§ z=0

=

m

0

ÅÅÅÅÅÅÅÅÅÅÅ

4

p

y

k

´¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨≠¨¨¨¨¨¨¨¨¨¨¨¨¨Æ

2 m r êH1+m r L

{

i

j

jj1 + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

m r - 1

m r + 1

z

zz 3 x £ @Hy - y £ L J x - Hx - x £ L J y D

1

ÅÅÅÅÅÅÅÅ

3

0

r

Evaluating (1) at z = 0 gives

B

<

z

§

z=0

=

m

0

ÅÅÅÅÅÅÅÅÅÅÅ

4

p

which verifies (4).

>

B x

§ z=0

=

m

0

ÅÅÅÅÅÅÅÅÅÅÅ

4

p

2 m r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

1 + m r

3 x £ @Hy - y £ L J x -

3 x £ Å -z £ i

Ä

Å

Å

Å

Å

Å

Å

Å Ç

m r - 1

m r + 1

j

jjJ y Hz £ L + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

k

1

Hx - x £ L J y D ÅÅÅÅÅÅÅÅ

3

0

r

J y